Formation of Social Values through the Use of Kulisusu Language in North Buton Regency Elementary School Students - Acoci; Muhammad Yusnan; Irman Matje; Wa Ode Nurfita Sari (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Kulisusu language is one aspect of culture that can shape a person's identity and enrich the culture of students in North Buton Regency. In an educational context, the use of Kulisusu language can help students understand local values and culture around them. The aim of this research is to determine the formation of social values through the use of the Kulisusu language among elementary school students in North Buton Regency. This research is a qualitative descriptive research, using Field Research type of research, which is based on the results obtained through field research. Regarding the objects discussed in accordance with the reality that occurs in elementary schools in North Buton Regency. The approach used in this research is a semantic approach. The semantic approach is an approach to looking at speech forms and interpreting speech forms in the Kulisusu language. The data source required in this research is data obtained from informants or informants, in this case teachers who were randomly assigned to 20 teachers. The type of data used in this research is the use of the Kulisusu language. Data collection techniques use field observation with a persuasive approach to teachers, and interviews are conducted to obtain research results that are in accordance with the research. The results of this research show that the role of the Kulisusu language in increasing social values among students, thereby facilitating effective interpersonal interactions and encouraging the introduction of cultural identity. Concretely preserving local languages and culture, including including regional language education in the curriculum and promoting local media that uses regional languages. With this holistic approach, students can strengthen their cultural identity and pass it on to future generations